System with mobile and intelligent monitor for the study of environmental care - Calderón Chavarri, Jesús Alan (2025)
This paper describes and proposes different engineering techniques for designing an intelligent system focused on environmental protection, based on stationary and mobile subsystems for monitoring physical variables. The variables selected for monitoring were water level, flow rate, pH, vibration, and surface water temperature, which are transmitted via radio frequency to an external monitoring center and a mobile unit. This system was designed using an optimized analysis of polynomial models to correlate each measured physical variable. Furthermore, this research also integrates the measurement subsystems through wireless data transmission between the sensors and the stationary and mobile receiving centers. This allows for the consolidation of all measured data to obtain a comprehensive view of the main target, such as a lake or river. Such bodies of water can cause serious damage in cities when adequate prevention measures are not in place, as occurs during the El Niño Southern Oscillation (ENSO) phenomenon in Peru. Therefore, this research seeks to contribute to prevention efforts through the described and designed system. A mechatronic system was designed, consisting of a drone as a mobile station data analyzer. The data collection point for the proposed monitoring center could be located at a site chosen by the community that would use the proposed system. For the experiments, prototype designs were prepared to collect the data measured by the sensors, most of which relied on nanostructures attached to the drone to measure temperature, pH, and water level. This data was processed by the drone's controller and the monitoring system. The data was collected from the Rímac River in Peru between July 2024 and September 2025, with the expectation that the proposed research will be useful to the communities during future ENSO even.